Does ERCP position matter? A randomized controlled trial comparing efficacy and complications of left lateral versus prone position (POSITION study) - Varma, Poornima; Ket, Shara; Paul, Eldho; Barnes, Malcolm; Devonshire, David A.; Croagh, Daniel; Swan, Michael P. (Endoscopy International Open, 2022)
Background and study aims Endoscopic retrograde cholangiopancreatography (ERCP) is traditionally performed with patients in the prone position (PP). However, this poses a potentially increased risk of anesthetic complications. An alternative is the left lateral (LL) decubitus position, which is commonly used for endoscopic procedures. Our aim was to compare cannulation rate, time, and outcomes in ERCP performed in LL versus PP.Patients and methods We conducted a non-inferiority, prospective, randomized control trial with 1:1 randomization to either LL or PP position. Patients > 18 years of age with native papillae requiring a therapeutic ERCP were recruited between March 2017 and November 2018 in a single tertiary center.Results A total of 253 patients were randomized; 132 to LL (52.2 %) and 121 to PP (47.8 %). Cannulation rates were 97.0 % in LL vs 99.2 % in PP (difference –2.2 % (one-sided 95 % CI: –5 % to 0.6 %). Median time to biliary cannulation was 03:50 minutes in LL vs 02:57 minutes in PP (P = 0.62). Pancreatitis rates were 2.3 % in LL vs 5.8 % in PP (P = 0.20). There were significantly lower radiation doses used in PP (0.23 mGy/m2 in LL vs 0.16 mGy/m2 in PP, P = 0.008) without a difference in fluoroscopy times.Conclusions Our analysis comparing LL to PP during ERCP shows comparable procedural and anesthetic outcomes, with significantly lower radiation exposure when performed in PP. We conclude that ERCP undertaken in the LL position is not inferior to PP, except for higher radiation exposure, and should be considered as a safe alternate position for patients undergoing ERCP.